The Effect of Trichoderma on N, P, K Soil and Corn Plants - Syamsiyah, Jauhari; Hartati, Sri; Herdiansyah, Ganjar; Maro'ah, Siti; Nurrahma, Rizkia Aufa (JOURNAL OF TROPICAL SOILS, 2024)
The use of Trichoderma is one effort to manage healthy and environmentally friendly plants. This fertilizer is part of organic fertilizer; which farmers do not widely practice yet. This fertilizer has an impact that can increase nutrients and soil fertility. This study examined the impact of using Trichoderma in combination with NPK fertilizer on soil nutrient, nutrient uptake, and growth of corn plants. A Completely Randomized Block Design consisting nine treatments with three replicates was applied. The treatments were Control (A), standard NPK (Urea 350 kg ha-1, SP-36 200kg ha-1 and KCl 75kg ha-1) (B), ¼ NPK + 5 kg ha-1 Trichoderma (C), ½ NPK + 5 kg ha-1 Trichoderma (D), ¾ NPK + 5 kg ha-1 Trichoderma (E), 1 NPK + 5 kg ha-1 Trichoderma (F), ¾ NPK +1.25 kg ha-1 Trichoderma (G), ¾ NPK +2.5 kg ha-1 Trichoderma (H), ¾ NPK + 3.75 kg ha-1 Trichoderma (I). The results showed that NPK fertilizer accompanied by Trichoderma increased soil total N by 84.21%, available P by 36.25%, and available K by 142.22%. The same treatment also increased corn plants’ N, P, and K nutrients by 52.71%, 106%, and 61.53%. The growth of maize plants from applyingTrichoderma up to 5 kg ha-1 has not reduced the use of NPK fertilizer yet. However, applying Trichoderma could improve soil fertility.